ATRT-15. LY6D – A CANDIDATE FOR NANOPARTICLE-BASED TARGETED THERAPIES OF ATRT. (4th December 2020) - Hagemeier, Lea; Sönksen, Marthe; Moreno, Natalia; Ettlinger, Romy; Bunzen, Hana; Kerl, Kornelius
Abstract: Atypical Teratoid Rhabdoid Tumors (ATRT) are aggressive brain malignancies of the infant. Despite intensive multimodal therapy, the overall prognosis remains poor, making investigations on targeted therapies crucial. Arsenic trioxide (ATO) is known to inhibit cell growth of ATRT in vitro and in vivo but its efficacy in solid tumors is limited by its adverse effects. We aimed to characterize whether a nanoparticle-based drug delivery could overcome these limitations. Therefore metal-organic frameworks containing ATO (MOF-ATO) were constructed. To improve drug specificity further, we searched for unique proteins on the surface of ATRT, in order to create antibody-drug-conjugates out of MOF-ATO and an ATRT-specific ligand. ATRT are marked by a biallelic loss of SMARCB1, which results in an activation of the repressive histone methyltransferase EZH2. After chemical inhibition of EZH2 with GSK126, a mass spectrometric based screening for differentially expressed surface proteins was performed. Treatment with ATO, as well as MOF-ATO and GSK126 each reduces the cell viability of ATRT cell lines. It results in a cell cycle arrest and an induction in apoptosis, being analysed via MTT test and flow cytometry. GSK126 treatment causes a significant upregulation of several cell surface proteins, upon them the Lymphocyte antigen 6 family member D (LY6D). Being rarely expressed on other human cells, this protein is an interesting candidate. An antibody-drug-conjugate consisting of MOF-ATO and LY6D-ligands could be a promising approach for future targeted therapies of ATRT.